El Niño-like tropical Pacific ocean cooling pattern during the Last Glacial Maximum - A. Hou; L. Jonkers; H. L. Ford; S. L. Ho (Communications Earth & Environment)
Abstract Many state-of-the-art climate models are unable to reproduce the observed 20th century surface warming pattern in the tropical Pacific Ocean, casting doubt on the robustness of future projections. Here, we examine past changes in the tropical Pacific upper ocean spatial pattern using paleoclimate reconstructions from proxies and simulations from a multi-model ensemble. The proxy results demonstrate that during the Last Glacial Maximum, when atmospheric carbon dioxide concentrations were lower than present, temperatures in the western tropical Pacific Ocean decreased more than in the east, leading to an El Niño-like cooling pattern. This result contrasts with the zonally uniform cooling pattern observed in model simulations, highlighting the common issue of models overestimating the sensitivity of eastern tropical Pacific sea surface temperatures to greenhouse forcing. Our proxy results imply that the western Pacific may warm more than the east in response to future climate change, producing a La Niña-like surface warming pattern.